MARKETING RESEARCH OF THE IKEA BRAND IN POLAND - YUZYK, MARIIA; YUZYK, OLHA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The way to stay in the market and increase your income is to use the potential of modern marketing strategies. The article considers the essence of such concepts as competition, code of ethics, the halo effect in IKEA business. In recent years, IKEA has significantly strengthened its position in the global market. The challenges facing the IKEA industry are analyzed: you can't just do business as usual and count on profit growth; they must be vigilant and responsive to important trends and developments, otherwise they risk being left behind more flexible competitors. Qualitative and quantitative marketing research was conducted and analyzed among international master's students studying second year of a master's degree in international business at the Faculty of Management of the University of Warsaw on their perception of IKEA business. IKEA's mission is to create a better life for many people, so the customer's opinion is the most important. The peculiarities of the buyer's behavior when choosing IKEA products are studied: what needs the buyer satisfies when looking for products; what the client most often needs when choosing the IKEA range; convenience of purchase. Brands of national and world level, peculiarity of their positioning on the Polish market are considered.
Keywords: marketing research; brand perception by international students; code of ethics; customer behavior